2010
DOI: 10.1684/epd.2010.0345
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychiatric comorbidities in temporal lobe epilepsy: the value of structured psychiatric interviews

Abstract: Background Although many studies have demonstrated a high prevalence of psychiatric disorders in epileptic patients, most have used unstructured psychiatric interviews for diagnosis, which may lead to significant differences in results. Here we present a study evaluating the prevalence of major psychiatric comorbidities in a cohort of South Brazilian patients with temporal lobe epilepsy using a structured clinical interview. Methods Neuropsychiatric symptoms were analyzed in 98 patients (39 men and 59 women) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 86 publications
1
2
0
Order By: Relevance
“…Several previous studies have reported comparable prevalences to that found in this study, such as 35-35.8% in Ethiopia [16, 20], 35.5% in Iceland [21], 36.5% in the United States [12], and 37% in Europe [22]. However, some studies found signi cantly higher prevalence rates ranging from 45-80% [15,[23][24][25][26][27][28][29][30],…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Several previous studies have reported comparable prevalences to that found in this study, such as 35-35.8% in Ethiopia [16, 20], 35.5% in Iceland [21], 36.5% in the United States [12], and 37% in Europe [22]. However, some studies found signi cantly higher prevalence rates ranging from 45-80% [15,[23][24][25][26][27][28][29][30],…”
Section: Discussionsupporting
confidence: 77%
“…Differences in sample size, assessment instruments used, and epilepsy patterns may explain the variation in prevalence across studies. Unlike other studies that focused only on temporal lobe epilepsy, which has a higher risk of CMD [25], this study assessed all types of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…One out of three PWE has a diagnosis of a psychiatric disorder over lifetime [ 4 ]. The risk is higher in patients affected by specific forms of epilepsy, and prevalence values of 52% and 54% have been reported in patients with drug-resistant epilepsy and TLE, respectively [ 3 , 6 , 30 ]. Considering the type of epilepsy, personality and anxiety disorders have been reported to be more frequent in patients with idiopathic generalized epilepsy (IGE), while depressive and psychotic disorders appear to be more frequent in those with focal-onset seizures and drug-resistant epilepsy [ 2 , 31 ].…”
Section: Epidemiology Of Psychiatric Disorders In Patients With Epilepsymentioning
confidence: 99%
“…However, there is a notable rise of the awareness for neuropsychiatric comorbidities of epilepsy and the number of clinical ( 1 , 2 ) and preclinical studies ( 3 , 4 ) of comorbidities in epilepsy seems to grow over the years. Many clinical reports indicate that mental disorders are more common in patients with epilepsy than in the general population ( 5 8 ). In this regard, mood disorders are the most common, anxiety disorders the second most frequent and psychotic disorders the least frequent in people with temporal lobe epilepsy ( 5 ), psychoses being a little more widespread than personality disorders ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical reports indicate that mental disorders are more common in patients with epilepsy than in the general population ( 5 8 ). In this regard, mood disorders are the most common, anxiety disorders the second most frequent and psychotic disorders the least frequent in people with temporal lobe epilepsy ( 5 ), psychoses being a little more widespread than personality disorders ( 6 ). Such high prevalence of psychiatric disorders is frequently demonstrated among patients with epilepsy when compared them with the general population or with individuals presenting non-epileptic neurological conditions ( 7 ), even if it may vary a lot due to differences in study methods and heterogeneity of epilepsy syndromes ( 8 ).…”
Section: Introductionmentioning
confidence: 99%